Analisis Pengaruh Variabel-Variabel Moneter Terhadap Pertumbuhan Ekonomi Indonesia - Dinda Suryaningrum; Indah Suci Laraswati; Irene Callista Salam (Journal of Management and Creative Business, 2023)
With the progress of the times, of course we will follow the development of technology. One of them is the ease of buying and selling transactions. This research is purposeful and useful in order to know the impact of the influence of each related variable. This study uses a qualitative approach. The data source was obtained from the Central Statistics Agency (BPS). Descriptive method is the method used. The variables used in this study are the dependent variable, namely economic growth (Y), the independent variables are non-cash transactions (X1), inflation (X2), and interest rates (X3), while the type of data used is secondary data. For export data taken from 2010- 2021 in the main destination countries. The data analysis technique used in this study is multiple regression analysis. Data analysis was used using the classical assumption test method, which concluded that the t-test of non-cash transactions had a significant effect on economic growth, inflation had no significant effect on economic growth and interest rates had no significant effect on economic growth. Meanwhile, in the non-cash transaction f test, inflation and interest rates have a significant effect on economic growth. The determination and correlation show that the relationship between the Independent Variable and the Dependent Variable in this study can be said to have a strong or close relationship because it is close to 100%.